2022
DOI: 10.3389/fimmu.2022.787713
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 and the PKA Pathway Regulate ILC2 Populations Expressing IL-9 and ST2

Abstract: Type 2 Innate lymphoid cells (ILC2s) are tissue-resident immune cells activated by epithelial-derived alarmins upon tissue damage. They regulate immunity against helminth parasites and allergies by expressing type 2 immune response cytokines including IL-9, known to be critical for inducing and potentiating the immune response in such context. Although ILC2s are reported to be the main source of IL-9 in mice during N. brasiliensis infection, the mechanisms that regulate the expression of IL-9 in these cells ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In contrast to iILC2s, nILC2s are tissue-resident cells that produce more IL-9 after activation ( 152 ). IL-33 and TSLP activate IL-9 production by ILC2s which further induces IL-5 and IL-13 during helminth infection ( 41 , 42 , 154 ). Since ILC2s express IL-9R, ILC2-derived IL-5/IL-13 can be regulated in autocrine manner by IL-9 ( 41 , 154 ).…”
Section: Transcriptional Regulation Of Ilc2 Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to iILC2s, nILC2s are tissue-resident cells that produce more IL-9 after activation ( 152 ). IL-33 and TSLP activate IL-9 production by ILC2s which further induces IL-5 and IL-13 during helminth infection ( 41 , 42 , 154 ). Since ILC2s express IL-9R, ILC2-derived IL-5/IL-13 can be regulated in autocrine manner by IL-9 ( 41 , 154 ).…”
Section: Transcriptional Regulation Of Ilc2 Identitymentioning
confidence: 99%
“…IL-33 and TSLP activate IL-9 production by ILC2s which further induces IL-5 and IL-13 during helminth infection ( 41 , 42 , 154 ). Since ILC2s express IL-9R, ILC2-derived IL-5/IL-13 can be regulated in autocrine manner by IL-9 ( 41 , 154 ). Similar to T cells, IL-9 production in ILC2s depends on the transcription factor IRF4 ( 42 , 155 ).…”
Section: Transcriptional Regulation Of Ilc2 Identitymentioning
confidence: 99%
“…ST2 is a component of the IL-33 receptor and can help IL-33 to exert its function, which is commonly used as a marker for ILC2s identification. KLRG1 can induce ILC2s proliferation and IL13 production [13,14]. Recent asthma studies have indicated that ILC2s initiate and enhance allergic airway inflammation and steroid resistance [15][16][17].…”
Section: Introductionmentioning
confidence: 99%